A review on Empty Fruit Bunch (EFB) as feedstock / Johan Hayat Wira Pangkaja - Wira Pangkaja, Johan Hayat (Faculty of Plantation and Agrotechnology, 2018)
Elaeis guineensis is a palm species which usually called African oil palm. It is the main source of palm oil. It is from the west and southwest Africa, its species name which is guineensis is originating from the name of Guinea which is the name of an area in Africa, and not the nowadays country which now use that name. The species is also now planted in several countries including Malaysia, Indonesia, Central America, and also the West Indies. The other palm that closely related is the American oil palm Elaeis oleifera and also a more distantly related palm, Attalea maripa, are also used to produce the palm oil other than using Elaeis guineensis. Empty Fruit Bunch (EFB) is the by-product that are being produced when palm fruit is processed and separated from a fresh fruit bunch in the initial process of producing the palm oil. The EFB that are still unprocessed is existing as very wet whole EFB each weighing several kilograms while the processed EFB is a fibrous material. Feedstock is the material that in its raw form existing to supply a machine or industrial process. EFB as feedstock can help to solve the problems of the limited feedstock sources that have been an issue lately. A review was carried out to see whether the EFB is suitable as feedstock and to compare it with other existing sources of feedstock such as fossil fuel. From the result, we can see that EFB is suitable to be made as feedstock through a couple of processes. Oil palm EFB can help the oil palm industry in Malaysia to increase in economy and world market. EFB also can help to replace the non-renewable feedstock that are running out.